2022
DOI: 10.1152/jn.00403.2021
|View full text |Cite
|
Sign up to set email alerts
|

Physiological tremor is suppressed and force steadiness is enhanced with increased availability of serotonin regardless of muscle fatigue

Abstract: Although there is evidence that 5-HT acts as an excitatory neuromodulator to enhance maximal force generation, it is largely unknown how 5-HT activity influences the ability to sustain a constant force during steady-state contractions. A total of 22 healthy individuals participated in the study, where elbow flexion force was assessed during brief isometric contractions at 10% maximal voluntary contraction (MVC), 60% MVC, MVC, and during a sustained MVC. The selective serotonin reuptake inhibitor, paroxetine, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This serotonergic projection has the potential to have a profound impact on motor neuron excitability, increasing the efficacy of synaptic inputs by three-to five-fold [92]. It has recently been demonstrated that ingestion of paroxetine, a selective serotonin reuptake inhibitor which increases the availability of serotonin, decreased muscle force CV (i.e., increased steadiness) during contractions in unfatigued muscle, and during a two-minute fatiguing contraction at 20% of MVC [93]. Given the coherence between muscle force CV and the cumulative motor unit spike train, differences in CV between conditions have been suggested to reflect differences in common synaptic input [79].…”
Section: Neuromodulatory Pathwaysmentioning
confidence: 99%
“…This serotonergic projection has the potential to have a profound impact on motor neuron excitability, increasing the efficacy of synaptic inputs by three-to five-fold [92]. It has recently been demonstrated that ingestion of paroxetine, a selective serotonin reuptake inhibitor which increases the availability of serotonin, decreased muscle force CV (i.e., increased steadiness) during contractions in unfatigued muscle, and during a two-minute fatiguing contraction at 20% of MVC [93]. Given the coherence between muscle force CV and the cumulative motor unit spike train, differences in CV between conditions have been suggested to reflect differences in common synaptic input [79].…”
Section: Neuromodulatory Pathwaysmentioning
confidence: 99%
“…As tryptophan is a precursor to serotonin and kynurenine, its availability may influence the CNS. In addition, Henderson et al [ 36 ] demonstrated that enhanced serotonin availability decreases physical tremor amplitude and improves steadiness during a sustained isometric contraction of the elbow flexors with the presence of fatigue. Interestingly, Lomiwes et al [ 8 ] demonstrated that during moderate intensity walking, blackcurrant juice was able to lower the perception of exertion, with a strong trend ( p = 0.06) for an increase in perceived mood, alongside an inhibition of the neurotransmitter platelet monoamine oxidase-B.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have demonstrated that oscillations in force output within the alpha band can be modulated by a range of factors. These factors include changes in nociceptive input (Yavuz et al, 2015), enhancement of serotonin availability by pharmacological means (Henderson et al, 2022), and alterations in the demands of a visuomotor task (Laine et al, 2014). Of particular interest are changes in muscle length which have been shown to exert a direct influence on alpha oscillations in force output, with shorter muscle lengths being associated with an increase in physiological tremor (Jalaleddini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%